DAMPAK PEMBUANGAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) TERHADAP KESEJAHTERAAN SOSIAL MASYARAKAT DESA LAKARDOWO KABUPATEN MOJOKERTO - Wardani, Yoelanda Ananta Dhevi; Rusli, Muhammad; Upe, Ambo (WELL-BEING: Journal of Social Welfare, 2021)
The research aims to determine the impact of hazardous and toxic waste substances (B3) disposal toward the social welfare in Lakardowo village Mojokerto. The type of this research is descriptive qualitative. The data collection that used is by observation, interview and documentation with 10 people in Lakardowo village. The result of this research is the impact of hazardous and toxic waste substances (B3) disposal toward social welfarestarting from material, social and spiritual, such as reducing the income that hit the majority society as a farmer in Lakardowo village which feel the damage in their agricultural land and increasing the cost of living for clean water. The emerge of Dermatitis or itchy disease that mostly attacks children body as a result of using well water or water sources in Lakardowo village. The rise of conflict between two camps in the society that causing the reduce of spiritual activities and also customs, which make the social welfare in Lakardowo village unfulfilled.